Role of Social Media in Journalism to create News for Mainstream Media. A Survey of journalists of Sindh, Pakistan - Solangi, Jan e Alam; Chhachhar, Abdul Razaque; Nizamni, Muhammad Qasim (Annals of Human and Social Sciences, 2025)
In Sindh, Pakistan, the digital emergence of Twitter (X), Facebook, WhatsApp, and YouTube platforms has severely influenced journalism. In countries where the media infrastructure is underdeveloped, they are vital to real-time coverage, playing to the audience, and circumventing common media restrictions.The research study is restricted to the population of 300 working journalists in both the urban and rural Sindh, which represents the print, electronic and online media. It was administered through a structured Likert-scale survey that consisted of a quantitative cross-sectional survey. The demographics were well represented through stratified purposive sampling. Almost all, 88 percent of people use social media every day, and people post about breaking news online before mass media informs about them. The strong correlation of digital influence is proven by Pearson correlation (r = 0.67, p < 0.01). Adopt moral editorial codes, introduce digital literacy courses, enhance rural media facilities as well as develop partnership between online and older platforms.